El desempeño de la calidad del servicio en los servidores públicos de la Secretaría de Desarrollo Económico (SEDECO) en Morelia, Michoacán - Núñez Alonzo, María Guadalupe (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
It will analyze the quality in the service and its relationship with socio-psychological aspects (leadership, motivation, labor satisfaction and the quality of negotiation). In the Economical and Development Secretariat in Morelia, Michoacán, the application of these methods, techniques and the analysis of the information and descriptive statistics, that reflects the importance and the relationship which exists between each of the variables, dimensions and the indicators that influence positive or negatively. It must be conscious of the importance roll that it represents the public functionary in the quality of service, not just like a mere perform of norms and procedures that it has been set according with the applicable norm. just like direct speaker between the public sector and the customer and the only one capable of get their own needs, we must notice, that he is a public functionary who is in charge of promote the quality in the service, he has the responsibility of the judgment that the citizen make of the quality of service obtained.

Se analizará la calidad en el servicio y su relación con aspectos socio-psicológicos (liderazgo, motivación, satisfacción laboral y gestión de la calidad) en la ―Secretaría de Desarrollo Económico en Morelia, Michoacán‖; se aplicarán métodos, técnicas, análisis de la información y estadística descriptiva, que reflejen la importancia y relación que existe entre cada una de las variables, dimensiones e indicadores que influyen positiva o negativamente. Se debe ser consciente del papel tan importante que representa el servidor público en la calidad del servicio, no como un mero cumplidor de normas y procedimientos impuestos por la normatividad aplicable, sino como un interlocutor directo entre el sector público y el cliente y el único capaz de captar sus necesidades; debemos tomar en cuenta que es el servidor público el encargado de fomentar e incentivar la calidad del servicio, en él recae la responsabilidad del juicio que el ciudadano haga de la calidad del servicio recibido.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2014-0033; Liderazgo; Motivación; Satisfacción; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6024